Color Change and Compressive Strength of Novel Single-Shade Composite Resins Exposed to Staining Beverages - Molina-Gantiva, Juan P. (2026)
Aim of this work was to evaluate the color change and mechanical compression resistance of two high-esthetic resin-based composites (single-shade composite (SSC) and conventional composite with spheroidal zirconium silicate (CC)) after immersion in coffee, red wine, and Coca-Cola, using artificial saliva as a control, over 7, 15, and 30 days. For color assessment, shade was recorded using the VITA 3D-Master system and converted to CIE L*a*b* coordinates to calculate color change (∆E). Due to incomplete data at 15 and 30 days for some conditions, the temporal component was described descriptively, and a two-way ANOVA (resin × beverage) was applied. For compressive strength (MPa), disc-shaped specimens were tested using a universal testing machine, and a three-way ANOVA (resin × beverage × time) was performed. Results showed a progressive increase in discoloration, with greater magnitude in red wine and coffee, while Coca-Cola produced smaller and slower changes. Beverage type accounted for the largest proportion of variation in color change, and the resin-beverage interaction indicated differential responses depending on material type. Compressive strength varied with time and resin type, with small effect sizes and no significant interactions. Overall, the SSC exhibited higher compressive strength than the CC. In conclusion, clinical material selection should consider both dietary exposure to pigmented beverages and the resin type to minimize short- and medium-term esthetic and mechanical deterioration.